Fixed-Term Employee Layoffs: A Repercussion of the Company's Sustained Financial Losses - Chusmayanti, Amalia Destyna; Khayatudin, Khayatudin; Yoel, Siciliya Mardian (Estudiante Law Journal, 2025)
Progress in a company, entrepreneurs need workers to be able to help the company operate and make a profit . In reality, sometimes problems and financial crises are also experienced by companies. Suppose the company experiences continuous losses and is unable to pay the wages of all employees so that the company takes steps to reduce the number of its employees. The existence of a Fixed-Term Employment Agreement (PKWT) where the general term is contract workers, is considered very profitable. The Manpower Law Number 13 of 2003 and the Job Creation Law Number 11 of 2020 have regulated the workforce and termination of employment (PHK). The weakness of this law results in uncertain laws that require workers to accept layoffs. Can a company lay off workers because of continuous losses in the company and how are the regulations for workers' rights for a certain period after being laid off in the perspective of Government Regulation number 35 of 2021. There are also the results of this study, namely that companies that continue to experience losses for 2 consecutive years are allowed to lay off workers, but with this regulation, companies cannot be arbitrary in carrying out layoffs, and workers are bound by work agreements at a certain time according to the rules set by the government must receive compensation if the worker is laid off. The rules that have been set so far are not biased towards workers, which gives companies or employers the freedom to lay off workers.